Internally welded steel bars enhance the bonding between steel pipes and concrete and prevent disengagement and debonding - Yanfeng Deng; Haitang Zhang; Jingyao Ni; Nianchun Deng (Scientific Reports)
Abstract In this work, the bonding properties of steel pipes and concrete enhanced by internally welded steel bars are investigated, and a method to prevent debonding is proposed. A series of experiments and ultrasonic tests revealed that the internal welding of steel bars effectively improved the bond strength of the interface between the steel pipe and the concrete. A Q420qD steel pipe and C60 self-compacting compensating concrete were used in the experiment, and the filling was uniformly ensured by pumping and vacuum-assisted perfusion. The experimental results show that the concrete-filled steel tube structure has good compactness and stability, but the local voiding phenomenon indicates that the material may have voids or defects. The performance of HPB300 grade steel bars under dynamic loading is also evaluated through cube compressive strength tests and rollout tests. The tests revealed that with an increasing number of internally welded steel rings, the push-out length decreases, indicating better bonding performance. In addition, the finite element simulation and the comparison of experimental data further reveal the bond-slip characteristics of the internally welded reinforcement components of different internal forms of concrete-filled steel tubes, which provides not only important data support for the optimal design and dynamic calculation of concrete-filled steel tube structures but also a reference for subsequent material repair and reinforcement work.